Biological function of the soluble CEACAM1 protein and implications in TAP2-deficient patients. - Markel, G; Achdout, H; Katz, G; Ling, K; Salio, M; Gruda, R; Gazit, R; Mizrahi, S; Hanna, J; Gonen-Gross, T; Arnon, T; Lieberman, N; et al. (2004)
Interactions of natural killer (NK) cells with MHC class I proteins provide the main inhibitory signals controlling NK killing activity. It is therefore surprising to learn that TAP2-deficient patients suffer from autoimmune manifestations only occasionally in later stages of life. We have previously described that the CEACAM1-mediated inhibitory mechanism of NK cytotoxicity plays a major role in controlling NK autoreactivity in three newly identified TAP2-deficient siblings. This novel mechanism probably compensates for the lack of MHC class I-mediated inhibition. The CEACAM1 protein can also be present in a soluble form and the biological function of the soluble form of CEACAM1 with regard to NK cells has not been investigated. Here we show that the homophilic CEACAM1 interactions are abrogated in the presence of soluble CEACAM1 protein in a dose-dependent manner. Importantly, the amounts of soluble CEACAM1 protein detected in sera derived from the TAP2-deficient patients were dramatically reduced as compared to healthy controls. This dramatic reduction does not depend on the membrane-bound metalloproteinase activity. Thus, the expression of CEACAM1 and the absence of soluble CEACAM1 observed in the TAP2-deficient patients practically maximize the inhibitory effect and probably help to minimize autoimmunity in these patients.